Levels Politechnic Community Satisfaction to The Use of Lebuhraya Pantai Timur 2 - Rosmida binti Ab Ghani; Najah binti Mohd Nawi; Norhafiza binti Idris (Jurnal Konseling dan Pendidikan, 2018)
Construction of East Coast Expressway 2 (LPT2) has a large impact in being able to link the states on the East Coast in a time shorter than existing roads. This gives a more comfortable alternative ride to the local community and beyond. However, there are still complaints from users regarding the facilities and services provided in LPT2. Thus, a study carried out to determine the level of satisfaction of polytechnic communities against the use of LPT2. A total of 222 respondent from four polytechnic involved in this study. Analysis of the findings made by using descriptive statistic and T-test through the software Statistical Package for Social Science (SPSS) version 23. Results of this analysis showed a mean value for items 'security level' in LPT2 is 2.29, i.e. at low mean score. While the 'facilities provided' is 2.50, where the stage score mean intermediate. Analysis of T-test also found, there is no significant relationship between the levels of satisfaction of users of different gender. Pearson correlation analysis found that the relationship between the usage frequency of LPT2 and the user satisfaction level was weak, but significant. It is hoped that the findings could help provides an overview of the level of satisfaction of the security aspects of polytechnic communities and facilities in LPT2.  This can help the parties responsible for providing the best service to oversee and improve LPT2 in all aspects in order to provide optimum satisfaction to the user.